A systematic review of economic evaluation studies of health technologies in the Philippines - Albania, Mattew P.; Defensor, Cyro Angelo; Largo, Brainy Luv A.; Gloria, Mac Ardy J. (Manila Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2025)
Introduction: The Universal Healthcare Act established health technology assessment as a transparent, evidence-based tool to guide the Department of Health and PhilHealth in setting priorities. In 2020, a guidance document was released to standardize the conduct of assessments, including economic evaluations. However, there remains no synthesized evidence on the status of economic evaluation studies of health technologies in the Philippines following its dissemination.

Objective: This study was conducted to systematically review the economic evaluation studies of health technologies in the Philippines following the dissemination of the official guidance document. Specifically, this study aimed to determine their quantity, characteristics, quality, and application. It also determined the association between the quality and application of the studies.

Methods: Electronic databases, repositories, libraries, and grey literature were searched to identify studies that fit into the eligibility criteria of this review. The general and study-specific characteristics of these studies were extracted. The quality of studies was assessed according to reporting and methodology using four different tools. Association between quality and application was determined through Fisher's exact probability test.

Results: The search yielded a total of 26 eligible studies. They were primarily cost-utility
analyses, mathematical model-based, conducted from a health system perspective, and
focused on medicines. No study contained equity considerations. Fourteen (52.85%) of
the studies were determined to have good quality. Eight (30.77%) were of moderate
quality, while the remaining were of low quality. Only eight (30.78%) studies informed
policies and decision-making. And no association was found between quality and application.

Conclusion: The multiple reporting and methodological flaws evident in the studies reinforce the need for deliberate efforts toward capacity-building of researchers, refining the guidance document, and strengthening its dissemination to improve the design, reporting, and conduct of economic evaluation studies in the country and promote a more equitable health system.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, May 2025
Keywords: Health technology assessment $x -- Economic evaluation -- Systematic reviews -- Philippines; Medical technology -- Cost effectiveness -- Health care decision making -- Philippines